Efeitos de diferentes terapias de reposição hormonal sobre a pressão arterial e balanço mineral ósseo de ratas castradas - Véras, Wagner de Brito (2005)
The estrogen has an important role in the homeostatic regulation of some tissues of the organism, good illustrated by the pathophysiologics alterations that occur in its deficiency, in the menopause. With the objective to brighten up these alterations, the use of the hormonal replacement therapy (HRT) in the aftermenopause has been studied, in function of its benefits in the prevention of osteoporosis and cardiovascular diseases. However, the traditional HRT with estrogen is associated with a bigger incidence in the development of cancer of breast and endometrium. One of the alternatives for the hormonal replacement is isoflavones (phytoestrogens derivatives of the soy) and the raloxifene (SERM). This study it has as objective to evaluate the possible effect of 17-β -estradiol, isoflavones and raloxifene on rats ovariectomyzeds throught of the measure of the arterial pressure, bone and plasmatic calcium and phosphorus concentration, corporeal, left ventricular and uterine weight. Adult Wistar rats had been divided in five groups (n=8). A group has controlled (C), a castrated group (CC) and the groups castrated and dealt with estrogen (CE), isoflavone (CI) and raloxifene (CR). Ten weeks after the ovariectomia, initiated the treatment of groups CE, CI and CR that lasted 12 weeks. In the end of the treatment, the direct measure of the pressure arterial and collected samples of blood was made, whose concentration of calcium and match had been measured. The animals had been, then, sacrificed to analyze the humid and dry weight of thighbone right and left, left ventricle and uterus, beyond the analysis of the concentration of calcium and match of thighbone. The treatment with 17-ss-estradiol, isoflavonas and raloxifeno did not modify the blood pressure levels of the rats. Groups CE and CR had gotten the lesser plasmatic levels and the biggest bone calcium levels. Group CR presented the lesser level of plasmatic match and groups CE and CR had presented the lesser levels of bone match. Group CE got the lesser profit of corporal weight. How much to the weight of thighbone, biggest groups CE and CR had gotten the profit of bone mass. The left ventricle presented bigger weight in group CE, as well as the weight of uterus. 15 On the basis of the gotten results, we conclude that the treatments with isoflavone and the raloxifene had presented greaters benefits, when comparative to the treatment with 17-ss-estradiol, therefore they had increased the calcium concentration and the bone mass without modifying the arterial pressure and nor the tropism of the cardiac and uterine cells